1995
DOI: 10.1128/iai.63.9.3411-3416.1995
|View full text |Cite
|
Sign up to set email alerts
|

Initial serum antibody titer to Porphyromonas gingivalis influences development of antibody avidity and success of therapy for chronic periodontitis

Abstract: This study assessed the effect of periodontal therapy on specific serum antibody concentration, expressed as titer, and antibody binding strength, expressed as relative avidity. The immune responses to Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans were investigated. Antibody titer was assayed by enzymelinked immunosorbent assay (ELISA) and relative avidity was measured by thiocyanate elution in 17 adult periodontitis patients before and after therapy. Immunoglobulin G (IgG) avidities (expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 36 publications
1
46
1
Order By: Relevance
“…Successful treatment results in the elimination of the aetiological agents and maturation of the immune system to produce antibodies of high avidity (Chen et al 1991). Mooney et al (1995) found an increase in IgG avidity to P. gingivalis (p 5 0.05) 6 weeks after hygiene phase therapy. In the present study, IgG avidity tended to increase post-treatment for the majority of the organisms tested, but generally this finding did not reach statistical significance for most of the test bacteria.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Successful treatment results in the elimination of the aetiological agents and maturation of the immune system to produce antibodies of high avidity (Chen et al 1991). Mooney et al (1995) found an increase in IgG avidity to P. gingivalis (p 5 0.05) 6 weeks after hygiene phase therapy. In the present study, IgG avidity tended to increase post-treatment for the majority of the organisms tested, but generally this finding did not reach statistical significance for most of the test bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…The main difference between that study and the current study is that the former investigation examined a group with generalised aggressive periodontitis patients who required extensive and repeated treatment over a period of time, and this may have boosted their humoral immune response. Mooney et al (1995) showed elevated antibody titres to A. actinomycetemcomitans 6 weeks after the completion of therapy. Their results, in addition to those of Chen et al (1991), showed increased antibody titres to A. actinomycetemcomitans and P. gingivalis, respectively, for the seronegative patients after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…First, as discussed by Mooney et al ., periodontal treatment may result in an inoculation effect leading to an increase in antibody to P. gingivalis GroEL-specific peptide. At the same time the reduction in antigen load resulting from improved oral hygiene and the use of antibiotics post-surgically, or from a combination of these mechanisms [17], may result in a reduction in the total burden of infection and a subsequent reduction in antibody to all bacterial GroEL which includes antibody to P. gingivalis GroEL. The combination of this reduction in the total burden of infection together with the inoculation effect may explain why some patients show an increase in antibody to human HSP60 while others show a decrease.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the host responds to oral bacteria with generally elevated levels of antibody to putative oral pathogens in both serum and gingival crevicular fluid in disease; however, some reports have suggested that severe generalized disease may show some decreased antibody levels (Califano et al 1999, Wang et al 2005, Takeuchi et al 2006, Hwang et al 2014. Treatment of periodontal disease is typically associated with early increases, but longer term decreases with successful therapy in antibody specific for oral bacteria (Ebersole et al 1985, Mooney et al 1995, Beikler et al 1999, Sakai et al 2001, Yamazaki et al 2004. While many of these biomolecules have been detected in saliva and correlate with periodontal disease, a wide array of them have also been detected in serum associated with chronic inflammation related to the oral disease (Fain 2006, Zakynthinos & Pappa 2009, Wu et al 2010, Cierny et al 2014).…”
Section: Discussionmentioning
confidence: 99%